The Western Perspective on Islam: Reading the Legacy of Snouck Hurgronje on Islamic Studies - As'ad, Muhammad; Zainuddin, Muhammad; Hady, M. Samsul (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2023)
This article discusses the Western perspective on Islamic studies, particularly through the academic legacy of Snouck Hurgronje, a Dutch scholar known for his research on Muslim culture in Aceh and his influence on the Dutch colonial strategy in the Dutch East Indies. The author aims to answer two questions: what were the methods and characteristics of Islamic studies used by Snouck Hurgronje, and how do they differ from contemporary Islamic studies? Utilizing library research, it examines scholarly literature on Hurgronje, comparing his methods to current Islamic studies practices in Western universities and Indonesia. The article sheds light on Hurgronje’s role in introducing anthropology and ethnography to Islamic studies, noting his significant contributions to the development of ethnographic methods in this area. It suggests that his approach has been influential in shaping the study of Islam and continues to influence contemporary research methodologies in the field. However, the article also notes that 21st-century Islamic studies are fundamentally different from Hurgronje’s era, with a greater focus on insider researchers and a lack of imperialistic interests. These scholars, particularly those in Indonesian universities under the Ministry of Religious Affairs, have a significant influence on the field and continue the legacy of Hurgronje by using philological, anthropological, and ethnographic approaches to Islamic studies.